The unconscious in culture : the structuralism of Claude Lévi-Strauss in perspective / edited by Ino Rossi. - Rossi, Ino (E.P. Dutton & Co., Inc., 1974)
On a visit to the zoo, a little boy imagines what it would be like to be various animals, such as a hippopotamus or a penguin, and listens as his mother explains how all parents keep their young ones safe.